A universidade como morada para a diferença: uma discussão sobre o permanec(s)er dos residentes universitários - Souza, Sâmmia Rodrigues de (2024)
This study seeks to investigate how resident students of the Federal University of Ceará, welcomed as alterity, experience daily university life in order to construct a household, conceived as the idea of a "safe dwelling." It is understood that higher education in Brazil is a socio-historical institution that suffers from various conditions, possessing a strong racial and class determination over individuals who enter it, such that academic routine can be experienced as difficult for some groups of students, threatening their permanence at the institution. Furthermore, the general objective of this research is to understand the construction of a household in the face of experiencing university routine by resident students of the Federal University of Ceará. To assist in understanding the dynamics involving student retention, this research makes use of the theory of "student affiliation," by sociologist Alain Coulon, as well as the idea of "Radical Alterity," elaborated by Emmanuel Levinas. The research is qualitative in nature and uses a socio-economic questionnaire as a data production tool, as well as autobiographical narratives constructed through interviews. The group of interviewees comprises ten students living in university residences at UFC in Fortaleza. The analysis of the produced narratives is carried out using the empirical phenomenological method. The student narratives point to a university experience where dwelling is achieved through students' concessions to academic activities within institutional rules. These concessions include investing in projects of interest; promoting socialization spaces; and the Search for training outside of graduation that helps them fulfill the required activities. The creation of affective bonds and the existence of solidarity networks are important issues regarding the sensation of belonging, security, and the possibility of rest, facilitating the experience in the new learning environment. However, it is not enough. The accounts highlight the responsibility that the institution must have towards the students, regarding the evaluation of pedagogical practices, as well as welfare policies. Additionally, students highlight the repercussions of a deficient student base, as well as socio-economic and geographical issues in their academic paths, in order to call for the need for intersectional work by HEIs, since the traditional adaptive logic does not contemplate the alterities that now enter this other space of knowledge.